2019
DOI: 10.1038/s41531-019-0081-9
|View full text |Cite
|
Sign up to set email alerts
|

Contractile dysfunction and nitrergic dysregulation in small intestine of a primate model of Parkinson’s disease

Abstract: Bowel dysfunction is a common non-motor symptom in Parkinson’s disease (PD). The main contractile neurotransmitter in the GI tract is acetylcholine (ACh), while nitric oxide (NO) causes the relaxation of smooth muscle in addition to modulating ACh release. The aim of this study was to characterise functional and neurochemical changes in the isolated ileum of the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated marmoset, an established model of PD motor dysfunction. While NO-synthase inhibitor L-NAME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
1
8
2
Order By: Relevance
“…Previously Natale et al 29 reported a reduction in murine enteric dopaminergic neurons 1 week after MPTP treatment in the duodenum but not in the colon. Whilst we found no change in the number of TH-ir neurons in the colon, we have previously reported generalised reduction in the intensity of TH-ir staining in the ileum but not the actual cell numbers 27 suggesting that these neurons may not be as susceptible to the toxic effects of MPTP as the dopaminergic neurons of the substantia nigra were, or were better able to repair over time. However, because TH is a common enzyme in the biosynthesis of both dopamine and noradrenaline much of the sparse TH immunoreactivity in the colon is likely to be associated with the extrinsic sympathetic innervation 30 , which may explain why the selective dopaminergic toxin MPTP did not alter the TH-immunoreactivity in the myenteric plexus of the common marmosets.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Previously Natale et al 29 reported a reduction in murine enteric dopaminergic neurons 1 week after MPTP treatment in the duodenum but not in the colon. Whilst we found no change in the number of TH-ir neurons in the colon, we have previously reported generalised reduction in the intensity of TH-ir staining in the ileum but not the actual cell numbers 27 suggesting that these neurons may not be as susceptible to the toxic effects of MPTP as the dopaminergic neurons of the substantia nigra were, or were better able to repair over time. However, because TH is a common enzyme in the biosynthesis of both dopamine and noradrenaline much of the sparse TH immunoreactivity in the colon is likely to be associated with the extrinsic sympathetic innervation 30 , which may explain why the selective dopaminergic toxin MPTP did not alter the TH-immunoreactivity in the myenteric plexus of the common marmosets.…”
Section: Discussioncontrasting
confidence: 83%
“…In the current study we observed a significant but low-level inflammation exemplified by the lack of change in SOX-10 glial markers and an increase in GFAP- and S100β in the proximal but not in the distal colon. In our previous study 27 we did observe a modest but significant increase in the number of SOX-10-ir cells in the ileum following MPTP treatment, but the lack of change in the proximal and distal colon in this study may suggest a regional pattern in the expression of inflammation.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…These symptoms can all be related to constipation, which is a particularly troublesome NMS, and a well‐studied symptom of prodromal PD 5,7–11 . Constipation in PD is reported to involve a dysfunctional colonic musculature which causes slowed movement of bowl contents through the colon, and prolonged transit time has been reported previously in PwP 8,39,40 . In addition, there is an outlet type obstruction and difficulty with rectal expulsion.…”
Section: Discussionmentioning
confidence: 80%